The career markers of elite basketball coaches: A qualitative analysis. - Schinke, Robert J. (University of Ottawa (Canada), 1995)
In-depth open-ended interviews were conducted with six elite Canadian basketball coaches. The purpose of the interviews were to delineate the development of these coaches from their first athletic experiences to their current elite coaching status. The average age of the coaches was 51.5 years, and they had coached for an average of 19.7 years. The results of the present study identified the following seven chronological stages: early sport participation, national elite sport, international elite sport, novice coaching developmental coaching, national elite coaching and international elite coaching. As novice athletes, they were influenced by parents, sport instructors an accessibility to physical resources. Eventually, all became elite level athletes with high levels of commitment, talent and passion for sport. Some athletes chose to pursue their athletics to the highest international level, and therefore became national team members. When athletic careers ended, the coaches searched for possible ways to remain affiliated with sport. The novice developmental coaching stages reflected a search for appropriate coaching philosophies and skills. Concurrently, the developmental coaches sought out additional theoretical and applied wedge from coaching science courses and more knowledgeable master coaches. Due to their winning records and formalized coaching procedures, those sampled were all hired to work with university basketball teams. The differences between the national and international elite levels were minimal. However, those who opted to become international level coaches made a conscious decision to prioritize competitive results over all else. The implications of this research provide basketball coaches and sport scientists with one possible blue print for the professional development of elite coaches.
Keywords: Psychology, Industrial.